Prediction of potential habitat areas of Rhododendron delavayi in China based on maximum entropy model MaxEnt - Dong, Jian; Bai, Tian; Gao, Zhao-sheng; Yang, Song-wei; Zhang, Jing-li; Wu, Ya-wen (Frontiers in Forests and Global Change, 2024)
Rhododendron delavayi Franch. predominantly thrives in broad-leaved evergreen forests and bushes at altitudes of 1,200–3,200 meters. It favors a cool, moist climate and thrives in acidic soils. Due to its high ornamental, medicinal, and scientific values, understanding its ecological needs and optimal cultivation ranges is crucial. This study analyzing the key environmental factors and their thresholds affecting its distribution and predicts the future potential habitats of R. delavayi using existing distribution data alongside current and projected climate data. The results indicate that the primary environmental influencers are soil pH (4.9–5.4), precipitation in the driest month (10–20 mm), and altitude, contributing 41.8, 24.1, and 18.3%, respectively. It also shows a declining trend in suitable habitats: from 27.75 × 104 km2 under current conditions, to 3.69 × 104 km2 by the 2050s, and further to 2.65 × 104 km2 by the 2070s.